Development of learning modules in health education for grade VI - Dela Pena, Angelita Malicdem 1945-
This paper presents instructional materials in modular forms designed and developed for the purpose of teaching health education in Grade IV. Based on the findings in the internal evaluation and in the controlled try-out, the modules can be used to teach health concepts to fourth graders, to facilitate individualized learning among pupils, to foster greater pupil interaction and individual involvement and to encourage good decision-making.